Caracterização clínica, perfil lipídico e polimorfismos genéticos em pacientes com xantelasma palpebral - De Marchi, Miguel Ângelo (2014)
Eyelid xanthelasma (EX) is the most common type of xanthoma characterized by yellowish plaques in upper, lower or bilateral eyelid, of different shapes and sizes, asymptomatic and reveals deposit of cholesterol derivatives of low-density lipoprotein (LDLc). Objective: To characterize patients with EX considering clinical and demographic aspects, lipid profile and genetic polymorphisms of apolipoprotein E (apo E), apolipoprotein B (apo B), and LDL receptor (RLDL). Patients and Methods: 200 Caucasian subjects were studied, unrelated, divided into two groups matched by sex and age: G1 - 100 patients with EX and G2 - 100 individuals without EX. All subjects were clinically evaluated considering gender, age, signs, symptoms, location, laterality, color, time of appearance and evolution. A peripheral blood sample for analysis of genetic polymorphism of apo E-Hha I, apo B-Xba I and LDL receptor RLDL-Ava II, and lipid profile (total cholesterol - TC, and cholesterol fractions of low density lipoprotein - LDL, high density lipoprotein - HDL, very low density lipoprotein - VLDL and triglycerides - TG) was taken. Results: There was predominance of females in both groups. XP was more frequent in patients 50 to 59 years both in males (29.7%) as in females (30.2%). As the clinical predominance of type plate (>1 cm) (57%), light yellow color (90%), involvement of both sides (67%), bilateral upper location (60%) and eyelid extension upper proximal (76%). Mean time of appearance of XP was 54.7±35.9 months. Lipid profile showed desirable values for all variables except for serum TG and VLDL-C in controls (32mg/dL and 160mg/dL respectively), being significantly higher compared to patients (30mg/dL, P = 0.0086 and 148mg/dL, P = 0.0082, respectively). As the allelic and genotypic frequencies for apo E Hha I, the ε3 allele prevailed in patients (0.84) and controls (0.82). The same occurred with ε3/ε3 genotype (68% patients and 71% controls). The lipid profile in association with the apo E polymorphism- Hha I showed a significant increase in the serum levels of TG and VLDL-C in patients with ε3/ε3 genotype (median = 31; 155mg/dL; respectively). Patients with genotype X+X had increased levels of LDLc (median = 124mg/dL) and reduced levels of VLDL-c (median = 28 mg/dL) and TG (median = 140mg/dl). Conclusions: EX was predominant in female and sixth decade of life, being plate type, yellow color course, bilateral involvement, bilateral upper and location proximal upper eyelid extension the most frequent. The average time of onset of EX was approximately 5 years, with asymptomatic for most of them. Serum levels of TC, VLDL-cholesterol and triglycerides showed abnormalities in approximately half of patients with EX. The distribution of polymorphisms of apo E, apo B and RLDL and levels of TC, HDL-cholesterol and VLDL-cholesterol was similar in subjects with EX and controls. Polymorphisms apo E, apo B and RLDL are not associated with lipid profile.